Effects of Foliar Silicon Application, Seed Inoculation and Splitting of N Fertilization on Yield, Physiological Quality, and Economic Viability of the Common Bean - Bueno, Amanda Magalhães; Flores, Rilner Alves; de Brito Ferreira, Enderson Petrônio; de Andrade, Aline Franciel; de Lima, Frederico Raimundo Simões; de Souza Junior, Jonas Pereira [UNESP]; de Oliveira Abdala, Klaus; Mesquita, Marcio; de Mello Prado, Renato [UNESP] (Springer Nature, 2021)
Purpose: A field experiment was carried out to evaluate the effect of foliar Si application associated with inoculation of seeds and nitrogen management on the physiological quality and grain yield of common beans. Methods: The experiment was laid out in randomized blocks with a 5 × 2 × 2 factorial design (four replicates on common bean cultivar Pérola). The first factor was foliar Si application at the concentrations: 0, 1.0, 2.0, 3.0, and 4.0 g L-1 of silicon. The second factor was the effect of the presence or absence of seed inoculation, while the third factor was the splitting of nitrogen topdressing (120 kg N ha-1). Parameters evaluated were relative chlorophyll index (RCI), foliar N and Si contents, gas exchanges, grain yield, and economic viability. Results: Split fertilization of 60 + 60 kg N ha-1 at 20 and 40 days after emergence (DAE) showed better results of grain yield, approximately 41 % higher than splitting of 80 + 40 kg N ha-1 at 20 and 40 DAE, regardless of fertilization containing Si. Foliar Si application increased grain yield in the order of 10 % (uninoculated seeds) and 25 % (inoculated seeds), regardless of splitting of nitrogen fertilization, using the highest Si concentration (4.0 g L-1). Regardless of seed inoculation, the splitting of 60 + 60 kg N ha-1, associated with the application of 3.0 g Si L-1, resulted in the maximum grain yield, approximately 20 % higher than the control. Conclusion: Application of 2.0 g Si L-1 promoted differential profits of up to US$ 236.72 regardless of seed inoculation and splitting of N fertilization.
Keywords: Biological nitrogen fixation; Phaseolus vulgaris; Seed treatment; Stabilized alkaline silicate; Topdressing